1992
DOI: 10.1111/j.1471-6402.1992.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Diversity and Methodology in Feminist Psychology: Critique, Proposal, Empirical Example

Abstract: This article calls for a revision in the methodology of feminist psychological research because cultural differences can neither be investigated nor integrated without methodological change. A methodology that combines etic (objective, behavioral) and emic (subjective, phenomenological) approaches was demonstrated in an empirical investigation. White women did not differ from women of color in self‐ratings on several gender‐role stereotypic terms (etic data). However, the two groups differed significantly in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…To that end, Method 4.A focuses on conceptual equivalence (Sue & Sue, 2000), whether a measure is assessing the same construct across different groups. As an example, demonstrating the problem of simply assuming conceptual equivalence, Landrine, Klonoff, and Brown-Collins (1992) administered several items of the Bem Sex Role Inventory (Bem, 1974) to White women and women of color (including Black, Latina, and Asian American). Participants were asked first to rate themselves on those items (e.g., ''passive,'' ''independent,'' ''feminine''), using a scale from 1 (never or almost never true of me) to 7 (always or almost always true of me), then to specify from a list their definition of that item.…”
Section: Component 4: Measurementmentioning
confidence: 99%
“…To that end, Method 4.A focuses on conceptual equivalence (Sue & Sue, 2000), whether a measure is assessing the same construct across different groups. As an example, demonstrating the problem of simply assuming conceptual equivalence, Landrine, Klonoff, and Brown-Collins (1992) administered several items of the Bem Sex Role Inventory (Bem, 1974) to White women and women of color (including Black, Latina, and Asian American). Participants were asked first to rate themselves on those items (e.g., ''passive,'' ''independent,'' ''feminine''), using a scale from 1 (never or almost never true of me) to 7 (always or almost always true of me), then to specify from a list their definition of that item.…”
Section: Component 4: Measurementmentioning
confidence: 99%
“…Survey researchers, for example, examine how survey items are interpreted by diverse samples and have critiqued research designs that assume construct equivalence across groups (e.g., Harachi, Choi, Abbott, Catalano, & Bliesner, 2006;Landrine, Klonoff, & Brown-Collins, 1992). In response to these and related concerns, statistical procedures have been developed to explore measurement equivalence such as testing moderating effects of group membership, computing reliability coefficients, and conducting an item response analysis (see Hui & Triandis, 1985;Knight & Hill, 1998).…”
Section: Conceptual Analysismentioning
confidence: 99%
“…There are several examples in survey research in which feminist scholars have focused on developing critical questions about how meanings are deployed in quantitative designs. For example, Landrine, Klonoff, and Brown-Collins (1992) asked a sample of women of color and White women to rate themselves on genderstereotype attributes (e.g., "I am sensitive to the needs of others"; "I am feminine"; "I am assertive") and, in addition, had participants circle the definition of the attribute that best matched what they had had in mind when they rated themselves. Landrine and colleagues (1992) found that groups did not rate themselves differently when evaluating their genderstereotype attributes; however, there were important differences in how terms such as "assertive" and "sensitive to the needs of others" were defined.…”
Section: Feminist Interventions In Conceptual Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Comme le suggèrent Allen et Barber (1992), la critique féministe de la pensée positiviste est fondée sur la prise de conscience que la réalité sociale n'est pas, et n'a jamais été sans contexte. Lather (1991) Certaines théoriciennes ajoutent que la recherche empirique traditionnelle reproduit les relations du système patriarcal (Landrine et al, 1992). Par exemple, la relation de pouvoir qui existe entre « chercheur/euse/s expert/e/s » et « participant/e/s, objet de recherche ».…”
Section: Survol De Différents Cadres éPistémologiquesunclassified